EFEKTIVITAS MEDIA PEMBELAJARAN MY CLASSROOM CREATION WALL DALAM MENINGKATKAN KEMAMPUAN LITERASI SAINS PESERTA DIDIK - Noviarni Ardillah (Jurnal Pena Karakter, 2020)
This research to describe the scientific literacy ability, implementation of learning, and students’ response to My Classroom Creation Wall media based learning. This type of research is descriptive quantitative research with one group pretest posstest design. The samples used in the study were students of class VI SD Negeri Krampyangan. The implementation of learning 1, 2, and 3 consecutive on reach score 3,80; 3,84; and 3,98. The result showed the implementation of learning get good category. Reliability of the learning observation instrument 1, 2, and 3 consecutive on reach score 99,2%; 98,29%; 99,80%. The result showed the observation instrument used is reliable. The improvement of students’ scientific literacy ability is significant and high improvement with the average of N-Gain of 0,72. The data of students’ responses showed that most of students (96%) are happy to My Classroom Creation Wall media based learning. The implication of the research is that the My Classroom Creation Wall media based learning can improve students’ scientific literacy ability.